History and Development of Modern Forensic Science (Criminalistics) in the Republic of Azerbaijan - Aliyev, Bakhtiyar Abdurahman ogly; Алієв, Бахтіяр Абдурахман огли; Алієв, Б. А. (Одеса : НУ «ОЮА», 2026)
In the modern life it is increasing importance of the lawyersʼ specialty, conditions of the Azerbaijan society and developing in this direction. Also, it is action formalizing general conception about importance of the preparation and creation the new, wide and special lawyersʼ knowledge. Such experts should have the following qualities: based on logical activity; highly developed, special and seriously preparing on own professional activity; quick adapting to the hard conditions of implementations of the law. Professional development and skills in using information technology are necessary to have for modern lawyers in Azerbaijan in this case, existing three stepped high educational system in our country has such specific expertsʼ features. In this article reader could be interested in conducting of criminalistic education, especially, in preparation of high qualified criminalists and forensic experts, and also development in educational sphere.
Aliyev B. History and Development of Modern Forensic Science (Criminalistics) in the Republic of Azerbaijan. Криміналістика майбутнього: цифрові інновації, штучний інтелект, глобальні виклики та загрози: збірник матеріалів міжнар. наук.–практ. конф. (м. Одеса, 5 черв. 2026 р.) / заг. ред. С. Ківалова, М. Аракеляна. Одеса : НУ «ОЮА», 2026. С. 52-59. URL: https://doi.org/10.32837/11300.33524
Keywords: criminalistics; legal knowledge; professional training; teaching; skill; practical activity